Budgeting Raw Material And Internal Control At Espotam Moex - Estina Sativa; Hesniati Hesniati (ConCEPt - Conference on Community Engagement Project, 2023)
Internal planning and management are essential for MSMEs. Internal management problems at Espotam Moex are in the form of the absence of budget planning for raw materials for each month. The implementation of business running activities has not been carried out properly; in this case, the Standard Operating Procedure (SOP) is not written to be known by employees, and sales records still use record keeping in the pocketbook, so it is not easy to know the sales every day or every month. This condition was known when visiting Espotam Moex by observing, interviewing store owners and supervisors, and carrying out a series of documentation as information in the design. The results of these activities are in the form of Standard Operating Procedure (SOP) in PDF and hardcopy form, raw material budget planning using Google Sheets, and sales recording forms in Microsoft Excel and hardcopy forms. Other than those, it is necessary to consistently update SOPs in quality improvement, and Espotam Moex can develop its business along with recording sales using the system in the future.